The Irish Johne's Control Programme - Gavey, Lawrence; Citer, Lorna; More, Simon J.; Graham, David (Frontiers in Veterinary Science, 2021)
The Irish Johne’s Control Programme (IJCP) provides a long-term approach to the voluntary control of Johne’s disease (JD) in Ireland, strongly supported by Irish cattle industry leadership. It leverages the establishment of Animal Health Ireland for control of animal diseases not regulated by the European Union. The IJCP has four objectives: facilitate protection against spread of JD to uninfected farms, reduce the level of infection when present, assure markets of JD control in Ireland, and improve calf health and farm biosecurity. Key IJCP elements are an annual veterinary risk assessment and management plan (VRAMP), annual whole herd test (WHT) by ELISA on blood or milk samples with ancillary faecal PCR testing of ELISA reactors, and Targeted Advisory Service on Animal Health (TASAH) investigations of infected herds. There are pathways for assurance of herds with continuing negative tests and for management of test-positive herds. Herdowners are responsible for on-farm activities, and specifically-trained (approved) veterinary practitioners have a pivotal role as technical advisors and service providers. The programme is supported by training of veterinarians, performance of testing in designated laboratories, documentation of policies and procedures, innovative data management for herd and test activities and for programme administration, training, and broad communication and awareness activities. Tools and systems are refined to address emerging issues and enhance the value of the programme. An Implementation Group comprising industry, government and technical leaders sets strategic direction and policy, advised by a Technical Working Group. Shared funding responsibilities are agreed by key stakeholders until 2022 to support herds in the programme to complete requirements. Herd registrations have increased steadily to exceed 1,800. National bulk tank milk surveillance is also being deployed to identify and recruit test-positive herds with the expectation that they have a relatively high proportion of seropositive animals. The programme will continue to innovate and improve to meet farmer and industry needs.